(untitled) (KONFERENSIYA, 2026)
The concepts of word and term occupy a central place in linguistics and terminology studies. While both function as lexical units of a language, they differ in their scope, function, and degree of semantic specialization. This article examines the relationship and interdependence between the notions of “word” and “term,” highlighting their shared linguistic nature and their functional divergence. Special attention is given to the process of terminologization and determinologization, which demonstrates the dynamic interaction between general vocabulary and specialized terminology.